The Buddhist World of Southeast Asia. Donald K. Swearer. - Werner, Karel (Buddhist Studies Review, 1997)
The Buddhist World of Southeast Asia. Donald K. Swearer. (SUNY Series in Religion) State University of New York Press, Albany 1995. xiv, 258 pp. US$16.95. ISBN 0-7914-2459-6.